2023
DOI: 10.3390/ijms24065345
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthetic Derivative of Renieramycin T Right-Half Analog Induces Apoptosis and Inhibits Cancer Stem Cells via Targeting the Akt Signal in Lung Cancer Cells

Abstract: Akt is a key regulatory protein of cancer stem cells (CSCs) and is responsible for cancer aggressiveness and metastasis. Targeting Akt is beneficial for the development of cancer drugs. renieramycin T (RT) has been reported to have Mcl-1 targeting activity, and the study of the structure-activity relationships (SARs) demonstrated that cyanide and the benzene ring are essential for its effects. In this study, novel derivatives of the RT right-half analog with cyanide and the modified ring were synthesized to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…We conducted further exploration into the immune regulation of neurospoagioma through DC gene vaccines. CD133, a cell surface antigen, has been identified on the cancer stem cells of various solid tumors, including neurospoagioma [ 57 , 58 ]. The enrichment of CD133-positive neurospoagioma stem cells has been linked to a highly tumorigenic population [ 59 , 60 ], which shows a negative correlation with patient survival.…”
Section: Vaccines In Immunomodulation Of Neurospoagiomamentioning
confidence: 99%
“…We conducted further exploration into the immune regulation of neurospoagioma through DC gene vaccines. CD133, a cell surface antigen, has been identified on the cancer stem cells of various solid tumors, including neurospoagioma [ 57 , 58 ]. The enrichment of CD133-positive neurospoagioma stem cells has been linked to a highly tumorigenic population [ 59 , 60 ], which shows a negative correlation with patient survival.…”
Section: Vaccines In Immunomodulation Of Neurospoagiomamentioning
confidence: 99%
“…According to previous studies investigating the structure-cytotoxicity relationship, which employed both in vitro and in silico approaches, the mechanistic pathways underlying the anti-lung cancer effects of marine alkaloids from the tetrahydroisoquinolinequinone family have been elucidated. Specifically, compounds such as 5-O-(N-Boc-L-alanine)-renieramycin T, a renieramycin-ecteinascidin derivative [20], (1R,4R,5S)-10-(benzyloxy)-9-methoxy-8,11-dimethyl-3-(thiazol-5-ylmethyl)-1,2,3,4,5,6-hexahydro-1,5-epimi-nobenzo [d]azocine-4-carbonitrile (DH_25), a right-half C-E ring analog of renieramycins [30], and 22-O-(4′-pyridinecarbonyl) jorunnamycin A, a 4′-pyridinecarbonyl substituted renieramycin-type derivative [29], have demonstrated efficacy against non-small cell lung cancer (NSCLC) cells through modulation of the protein kinase B (Akt), myeloid cell leukemia-1 (MCL-1), and mitogen-activated protein kinase (MAPK) signaling pathways, leading to the induction of apoptosis. The proteins Akt, MCL-1, and MAPK are interconnected targets of cellular signaling networks involved in the regulation of apoptosis.…”
Section: Molecular Dynamics Analysis Of Mapk1 and Mapk3 With 11mentioning
confidence: 99%
“…However, the observed compound was not interacting with residue Trp80 of Akt1 with - stacking interaction, which is one of the key interactions in the allosteric inhibition of Akt (75) The RT derivative DH_22 (Figure 6) is a novel compound synthesized based on the right-half structure of RT, or RM-based hybrid renieramycin-ecteinascidin derivative (28), which was isolated from the Thai blue sponge Xestopongia sp. We synthesized various derivatives of reniramycin from marine natural products as starting materials (76) and evaluated their biological activities. The results indicated that a compound was effective when aromatic rings (especially pyridine rings) were introduced in place of the angelate in the C-1 substituent of reniramycins (77,78).…”
Section: Inhibition Of Survival Regulators By Renieramycin T Derivati...mentioning
confidence: 99%